Seasonal variation in litter fall an age series gmelinaarborea plantation in a Nigerian rainforest (2013)
Monthly variation in litterfall of Gmelinaarborea stands aged 28, 29, and 30 years were studied for 13 months in 2005 - 2006 with litter traps in three 20m x 20m plots randomly selected in Gmelinaarborea stands in Shasha Forest Reserve (SFR),Osun State, Nigeria. Monthly collections of litter fractions per stands were sorted into leaves, twigs, reproductive structures and others. Litters according to fractions per stand per month were oven dried at 80°C for 48 hours. Samples were created for chemical analysis. Data collected were analyzed using descriptive statistics and inferential at 0.05 level of significance. Litterfall (especially leaf fall) occurred throughout the period of collection (13 months) in the stands (S). The peak of total litter fall was recorded in October 2005 in S1(18.2%) while peaks were recorded in September of same year in S2 (11.21%)and S3 (13.67%). The analysis of variance to determine interaction effect between fall of the litter fractions and age of the stands did not show any significant differences. Leaves constituted the bulk of litter fall across the three stands. The percentage of leaf litter to the total litter per hectare in stand ages 28, 29 and 30 years were 41.32, 34.19 and 24.48% respectively, while the contribution of unidentified litter thrash was highly insignificant.